Hubungan Antara Minat Baca Terhadap Prestasi Belajar Mahasiswa di Perguruan Tinggi Kota Pekanbaru - Asmawati; Thamrin Hasan; Diani Hartati (Perpustakaan Universitas Riau, 2021)
This study aims to determine the relationship between reading interest on student achievement in universities in Pekanbaru City. The method used is a survey with a correlational technique. Research respondents were active students totaling 300 people taken from 20 public and private universities located in Pekanbaru City, using quata sampling technique. The research instrument used a questionnaire, with a Likert scale model. The data analysis technique used is descriptive statistical analysis technique and inferential statistical analysis. The results showed that there was a relationship between reading interest on student achievement, with a correlation coefficient (R) of 0.068. The value of this correlation coefficient indicates that the level of strength of the relationship is very weak. And obtained the value of the coefficient of determination R Square (R2) of 0.005. This means that the effect of variable X on Y is only 0.50%. The results of this study are useful for the improvement and improvement of the development of reading interest, especially in universities in Pekanbaru City. The conclusions of this study indicate that student learning achievement can be increased by reading interest.